Prospective data collection of off‐label use of rituximab in Australian public hospitals. Issue 8 (6th August 2013) - O'Connor, K.; Liddle, C.
Abstract: Background: Rituximab is a chimeric, anti‐CD20 monoclonal antibody registered for the treatment of B‐cell malignancies and refractory rheumatoid arthritis in Australia. In addition to these approved indications, there has been growing interest in the use of off‐label rituximab in the management of a variety of diseases. Aims: To determine the current usage of off‐label rituximab in Australia, we collected nationwide data. Methods: Information regarding patients receiving rituximab for off‐label indications was prospectively collected for a 6‐month period from Australian public hospitals. Data recorded included clinical indication, dosing schedule, previous therapy and efficacy assessment. The level of evidence for the use of rituximab was determined for each off‐label indication. Results: During the 6‐month period, a total of 364 instances of off‐label rituximab use was recorded in the national database. A total of 63 underlying diagnoses was identified. These were subclassified into haematological disorders (19%), autoimmune connective tissue diseases (12%), vasculitis (12%), neurological disorders (12%), transplant‐related uses (12%), haematological malignancies (11%), muscle disorders (8%), renal diseases (6%), dermatological conditions (5%), other conditions (2%) and ocular diseases (1%). Forty per cent of these requests were supported only by level 4 evidence of benefit. Data highlighted the non‐standardised approaches to drug approval mechanisms, dosing schedules and monitoring for efficacy. Conclusions: Off‐label rituximab is prescribed for a diverse range of clinical conditions. Determining a safe and effective means of regulating this use within an evidence‐based framework remains an ongoing challenge.